2023
DOI: 10.3390/en16114280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tender Criteria for Electric and Diesel Buses in Poland—Has the Ongoing Revolution in Urban Transport Been Overlooked?

Abstract: The electrification of public transport is an overwhelming trend, representing the first step in the energy transition of the transport sector. The transport sector is characterized by the prevalence of public ownership and the significant influence of the public sector. Accordingly, tendering procedures are widely utilized to identify the most efficient bus delivery options. This paper compares, evaluates, and identifies the differences in criteria used in tenders for battery electric buses and diesel buses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The study concluded that diesel buses have the lowest TCO. The TCO of an electric bus has been found to be approximately 10 % higher than that of a conventional diesel bus [ 25 ]. It has been demonstrated in numerous studies that electric buses bring greater benefits in terms of energy efficiency compared to traditional diesel and hybrid electric buses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study concluded that diesel buses have the lowest TCO. The TCO of an electric bus has been found to be approximately 10 % higher than that of a conventional diesel bus [ 25 ]. It has been demonstrated in numerous studies that electric buses bring greater benefits in terms of energy efficiency compared to traditional diesel and hybrid electric buses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another issue with the charging of the EBs is the cost, and, therefore, the process of procuring and tendering is also challenging. [5] describes in detail the issues with the procurement process for the charging station for the EU market. The paper analyzed two methods, namely the total cost of ownership and the lifecycle cost analysis (both methods include a variety of costs, such as the vehicle cost, financing cost, tax, labour fee, maintenance, etc.…”
Section: Introductionmentioning
confidence: 99%